Comparison of standards or frameworks for IT service desk implementation - Firmansyah, Ardhi Dwi; Sulistiyani, Endang (Institute of Computer Science (IOCS), 2025)
The service desk plays a significant part in implementing Information Technology Service Management (ITSM). However, there are some hurdles to its execution. Currently, there are several ITSM standards and frameworks accessible. However, its application is not simple. Therefore, this study aims to analyze the characteristics of the IT Service Desk standard or framework. The Study of Similarity of Models and Standards (MSSS) method was used in this study. Starting from selecting standard selection criteria or frameworks, analyzing to find similarities and differences, to presenting results. There are four selected standards or frameworks, namely ITIL V3, ITIL 4, ISO/IEC 20000, and COBIT 2019. All of them define the same process regarding the implementation of the IT Service Desk. However, all of them have specificity. COBIT 2019 defines processes related to the IT Service Desk, namely DSS 02 and DSS 03. While ITIL V3 and ITIL 4 provide more detailed explanations related to the procedures of each process. ITIL V3 also defines how to build an IT Service desk, both in terms of organizational structure and role requirements. Meanwhile, ISO 20000:2018 provides an overview of how an organization is to comply with the standard